2013
DOI: 10.3390/pr1020128
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modeling for the Design and Cyclic Operation of an Atomic Layer Deposition (ALD) Reactor

Abstract: A laboratory-scale atomic layer deposition (ALD) reactor system model is derived for alumina deposition using trimethylaluminum and water as precursors. Model components describing the precursor thermophysical properties, reactor-scale gas-phase dynamics and surface reaction kinetics derived from absolute reaction rate theory are integrated to simulate the complete reactor system. Limit-cycle solutions defining continuous cyclic ALD reactor operation are computed with a fixed point algorithm based on collocati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…These models strongly depend on the use of proper ALD kinetics, whereas only empirical or simulation-based sticking coefficients are available. Travis et al [26][27][28] have recently shown how realistic ALD reaction and growth surface dynamics models can be derived from first principles, which, coupled with a proper precursor transport model, provides a valuable tool for dynamic optimization of ALD processes. For this reason, the adsorption kinetics and the surface coverage dynamics used in the present work is based on the work of Travis et al Here we briefly describe the adsorption kinetics and surface coverage dynamics model implemented in our precursor transport model; for further details the reader is referred to Travis et al [26][27][28].…”
Section: Adsorption Kinetics and Surface Coverage Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…These models strongly depend on the use of proper ALD kinetics, whereas only empirical or simulation-based sticking coefficients are available. Travis et al [26][27][28] have recently shown how realistic ALD reaction and growth surface dynamics models can be derived from first principles, which, coupled with a proper precursor transport model, provides a valuable tool for dynamic optimization of ALD processes. For this reason, the adsorption kinetics and the surface coverage dynamics used in the present work is based on the work of Travis et al Here we briefly describe the adsorption kinetics and surface coverage dynamics model implemented in our precursor transport model; for further details the reader is referred to Travis et al [26][27][28].…”
Section: Adsorption Kinetics and Surface Coverage Dynamicsmentioning
confidence: 99%
“…For this reason, for ALD on nanoparticles in FBRs, the dynamics of both the TMA and H 2 O exposures are modeled by coupling a multiscale precursor transport model with a detailed description of the adsorption kinetics and surface coverage dynamics. The latter is based on the kinetic model for TMA/H 2 O ALD recently developed by Travis et al [26][27][28] from absolute reaction theory, which we will briefly describe later. This kinetic model has the advantage that it uses no empirical or simulation-based sticking coefficients to describe ALD dynamics, as often done in other approaches [29][30][31].…”
Section: Multiscale Modelingmentioning
confidence: 99%
“…In the next paper, strategies for immobilizing titanium oxide powder as thin films on polymer substrates are developed and evaluated for the photocatalytic degradation of acetylsalicylic under both UV and solar light irradiation [13]. The area of hard materials is addressed in the next paper, where a mathematical model of a laboratory-scale atomic layer deposition reactor system is developed and used to discover limit cycle solutions and to gain insight into the effects of reactor design on deposition performance [14].…”
Section: Materials Process Engineeringmentioning
confidence: 99%
“…However, some changes in the symbols and the physical meanings differentiate the models and give other potential to the whole engineering part. Models are used everywhere for simulating any possible process [54][55][56][57][58][59][60][61][62][63][64][65][66]. The main models, which will be discussed in following, are the Freundlich, Langmuir, and Langmuir-Freundlich (L-F) equations.…”
Section: Isotherm Modelsmentioning
confidence: 99%